Integrated assessment of meso-level watershed development: progress of an integrated evaluation project in Andhra Pradesh - Syme, G.J.; Croke, B.F.W.; Ratna Reddy, V.; Ranjan, R.; Samad, Madar; Pavelic, Paul; Herron, N.; Rao, K.V.; Ahmed, S. (2010)
The issue of scale has become paramount for the effective evaluation of WSD programs. Shile terms vary from state to state, the following definitions have been adopted for this study and are deemed appropriate for Andhra Pradesh. Micro scale - less than 1500 hectares; Meso scale 1500 - 10000 hectares; Macro level over 10000 hectares (including basin level investigations). There is a need for a meso-scale benefit and cost evaluation of the WSD programs so that unintended impacts are avoided and that the implementation of programs is improved. Operating at a meso-scale will also provide more effective opportunities to link and address micro and macro scale biophysical and institutional issues. This project will integrate environmental, economic, social, equity and dimensions at meso levels to help ensure that WSD contributes positively to the Indian government's sustainable livelihoods goal and provide the foundations for a resilient and sustainable WSD. Success will not only be determined by spatial scale (e.g. micro versus meso) but will also be determined by the disciplinary scale of analysis (e.g. focusing on short term economic efficiency alone runs considerable risk of ignoring longer term trends in natural and social capital). This paper describes early progress on developing such an evaluation model.